(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
In order to study the effectiveness of the cotton ginning system of cotton gins in local cotton gins equipped with foreign technology, research work was carried out on the "Imperial" saw gin with 170 saws manufactured by the US company "Lyummus" in the cotton ginning enterprise "Karvon" of the Bukhara region. The research work was carried out in Bukhara-6 selection cotton with initial moisture content of 9.6% and 12.8%, dirtiness of 3.5% and 9.4%, grade I and III grade 2. As a result of the research, the contamination of cotton after the supplier-cleaner was equal to 1.0% and 1.4% on average according to the varieties. In this case, the cleaning efficiency of the supplier-cleaner was on average 24.2% and 27.5%, which showed that it was 5.8 (abs)% and 7.5 (abs)% less than the cleaning efficiency of the supplier-cleaner in the technical characteristics of gin. . During cleaning of high and low grade cotton, separation of cotton from the supplier-cleaner to waste occurred, and the amount of separated cotton was on average 18% and 25% in relation to the mass of waste. Gin productivity in ginning of ginned cotton was on average 1750 kg/h and 1210 kg/h, which showed average 24.5% and 26.8% less than gin passport productivity. The mass fraction of defective fiber and impurities in the post-ginning fiber was 3.56% and 4.83% on average, and seed hairiness was 15.56% and 17.3% on average.In this case, the hairiness of the seed was higher by 5.1 (abs) % and 5.8 (abs) % compared to the industry standard, and it was observed that along with the denatured seed, the fiber suitable for weaving was transformed into fluff. As a result of the conducted research, despite the fact that the cleaning efficiency of the "Imperial" chainsaw gin supplier is higher than the cleaning efficiency of the local gin supplier-cleaner, on average, 18% and 25% of the cotton is separated into waste when cleaning cotton from large impurities, and additional equipment and electricity are used to clean the cotton separated into waste. was studied. In addition, it was found that the gin supplier-purifier has a complex construction, which causes difficulties in its use and consumes 9 kW more electricity than the local gin supplier-purifier. Due to the fact that the foreign gin supplier-cleaner has the above-mentioned shortcomings, it was studied that it is necessary to improve the cleaning efficiency and improve the quality of cotton by improving the local gin supplier-cleaner.